2012
DOI: 10.7150/ijms.4563
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smokeless Tobacco “Maras Powder” Use on Nitric Oxide and Cardiovascular Risk Parameters

Abstract: Background: Smokeless tobacco use is common in various parts of the world. In Turkey a type of smokeless tobacco called “Maras powder” is widely used in southeastern region. Smoking is known to have an adverse effect on nitric oxide and cardiovascular risk factors. The aim of this study was to evaluate whether there is difference between the effects of Maras powder and cigarette smoking on the cardiovascular risk factors and nitric oxide levels.Methods: In the study, participants were 48 Maras powder users, 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
(37 reference statements)
3
17
0
Order By: Relevance
“…In a similar study, Maras powder use did not affect blood sugar concentrations [7], which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In a similar study, Maras powder use did not affect blood sugar concentrations [7], which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that Maras powder use increases oxidative stress and thus quickens atherosclerosis in addition to its negative effects on many tissues and organ systems [7,8,12–14]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 This suggests that L. buccalis may be involved in the etiology of many diseases seen in ST users, including genotoxic damage, 11 chronic respiratory diseases, 31 attention deficit hyperactivity disorder, 32 atrial conduction abnormalities, 33 and carotid intima media thickness. 34,35 Eribe et al 28 suggested that L. shahii and L. wadei are involved in the pathogenesis of OSCC. Thus, the greater numbers of L.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental and clinical studies have associated elevated UA levels with endothelial dysfunction and a reduction in nitric oxide (NO) levels [17]. Plasma NO levels were shown to be independently associated with MPV [18]. …”
Section: Discussionmentioning
confidence: 99%